Recent Advances in the Use of Drill Cuttings for Determining Subduction Zone Structure, Stratigraphy, and Stress State - P. H. Cornard; A. M. Schleicher; C. Regalla; M. Hamahashi; M. Kitamura; R. Fukuchi; K. T. Pickering; H. Kitajima; T. Wiersberg (Geochemistry, Geophysics, Geosystems)
Abstract Obtaining in situ samples from active subduction systems is critical for assessing the material properties and geological evolution of rocks and sediments that host plate boundary deformation, and advancing our understanding of the processes that lead to fault locking and rupture. However, accessing and coring these materials is challenging, and commonly requires riser drilling. The International Ocean Discovery Program (IODP) Nankai Trough Seismogenic Zone Experiment (NanTroSEIZE) project has successfully used ultradeep riser‐drilling to collect deep crust samples via core or cuttings. This paper reviews analytical methods and challenges associated with interpreting subduction zone processes from cuttings. A key advantage of analyzing cuttings is the ability to collect real time data on the lithological, biostratigraphical, structural and geochemical properties of the drilled materials. Combining these data with logging‐while‐drilling and mud gas logging data permits the generation of depth profiles of lithological variation and deformation structures. Significant limitations of cuttings include small sample size, contamination from cement and drilling fluids, the formation of drilling‐induced cohesive aggregates (DICAs), and vertical mixing during ascent. While it is impossible to overcome all these limitations, this study provides and includes examples illustrating how these issues can impact the assessment of the geological formation. Despite these challenges, cuttings have advanced our knowledge of subduction zone stratigraphy, fault friction, fluid flow, and stress distribution. This has significantly improved our understanding of earthquake mechanics, megathrust fault processes and locking/rupture mechanisms along plate fault boundaries. Future riser‐drilling operations are therefore crucial for understanding megathrust earthquakes and fault behavior.